Ethical questions in children sexual victimization research - Kovčo-Vukadin Irma (Temida)
Ethics in the research with children has become a very important topic due to an increasing number of research involving children resulting in an increasing number of academic papers on this topic. Conducting social research in the field of child sexual victimization presents double vulnerability: firstly, it involves research with a vulnerable population, and secondly, the topic itself is sensitive. This raises numerous ethical questions and can result in researcher’s unwillingness to explore this particular field. The aim of this paper is to answer the question of specific ethical challenges in researching sexual victimization of children. The specific questions addressed in the paper include the following: 1) Are there any specific ethical guidelines for researching child sexual victimization, and 2) What ethical questions are specifically addressed in child sexual victimization research? The answers provided on the basis of the analysis presented in the paper are: 1) There are no specific ethical guidelines for conducting epidemiology research of child sexual victimization, and 2) It is difficult to single out ethical questions specific for this research area from available literature (only few authors are addressing specific ethical issues in this type of victimization research). Therefore, it is concluded that more attention should be focused on ethical issues in epidemiologic research of child sexual victimization.